Once Upon a Time There Lived An Old Man and An Old Woman - Zaitseva, Irina (Russia : Krasnoyarsk Film Studio, 2004)
The story of an old man and old woman living in an abandoned village along the river Yenisei in Russia. The film’s focus is generational conflict: parents do not want to move to the city and the children are reluctant to stay in the village.